Pendampingan Pembinaan Syarhil Qur’an Berbasis Cooperative Learning untuk Pembentukan Karakter Religius Anak Migran di Malaysia - Sevia Nur Hidayatullah; Qurroti A’yun; Mohammad Darwis (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This community service initiative was motivated by the limited availability of sustained religious guidance for Indonesian migrant students at the PKBM PNF (Non-Formal Education Community Learning Center) of the Indonesian Embassy in Kuala Lumpur, particularly regarding the strengthening of religious character. This situation necessitated a learning strategy that focused not only on the cognitive aspects of religion but also on the internalization of religious character values ​​among students. The activity aimed to describe the implementation of Syarhil Qur’an training based on cooperative learning principles to strengthen the religious character of migrant students, specifically focusing on interpersonal ethics such as empathy, tolerance, and mutual respect. A service-learning approach was employed, comprising four stages: preparation, introduction, practice and guidance, and performance. The participants consisted of three Indonesian migrant students, supported by the implementation team, teachers, and PKBM administrators. The results indicate that the cooperative learning-based Syarhil Qur’an training successfully enhanced student participation, self-confidence, and collaborative skills. Furthermore, the internalization of religious character values ​​was evident in the students' empathy, tolerance, and mutual respect during social interactions, both within and outside the learning sessions. The program's novelty lies in the application of cooperative learning through the assignment of specific roles qari' (reciter), translator, and pensyarah (expositor) thereby transforming Syarhil Qur’an instruction into a medium for shaping the religious character of migrant students in an overseas non-formal education setting. Consequently, this training model offers an alternative approach to strengthening religious character within non-formal education environments.